Four decades of research on rice intercropping: A bibliometric analysis - S.M. Shahidullah; Bir Jahangir Shirazy; Md Abdur Rouf Sarkar; Md Khairul Quais (Journal of Agriculture and Food Research, 2024)
Intercropping stands as a crucial strategy in promoting sustainable crop intensification while optimizing the use of natural resources. Rice intercropping, predominantly prevalent in upland and deepwater ecosystems characterized by less favorable conditions, represents a crucial area of research within this context. To the best of our knowledge, no prior research has explored the landscape of rice intercropping through bibliometric methods. Using the comprehensive Web of Science database, we conducted a meticulous analysis of 187 articles spanning the years 1980–2022, employing specialized software tools such as VOSviewer, Biblioshiny, and OriginPro. These articles were authored by a diverse group of 561 researchers hailing from 68 different organizations across 36 countries and disseminated through 67 distinct journals. Notably, the average annual growth rate of publications in this field was found to be 5.37 %. Our findings reveal that India, China, Brazil, and Indonesia emerged as the leading countries in publishing rice intercropping research. Among the numerous organizations, South China Agricultural University secured the highest rank, closely followed by the Indian Council of Agricultural Research and the Consortium of International Agricultural Research Centers. The research landscape was further illuminated by identifying the three most prominent journals in which these articles were published: Indian Journal of Agronomy, Indian Journal of Agricultural Sciences, and Field Crops Research. Classification of these research publications into categories exposed the primary domains of interest, including agronomy, multidisciplinary subject, soil science, and environmental science. A keyword analysis unequivocally pointed to ‘intercropping’ as the focal point of interest within this research area. As we look to the future, it is imperative that forthcoming studies delve into the realms of mechanization in rice intercropping, soil microbiology, and harnessing solar energy for more efficient agricultural practices. This comprehensive review serves as a valuable reference for pinpointing research priorities in tackling global food security challenges.